A comprehensive study on the properties of polypropylene fibers and nonwovens in dependence of processing and storing conditions - Lanyi, Franz; Schubert, Dirk W. (Europe Africa Conference 2017 of the Polymer Processing Society, 2017)

A method to reveal bulk and surface crystallinity of Polypropylene by FTIR spectroscopy - Suitable for fibers and nonwovens - Lanyi, Franz; Wenzke, Nicolai; Kaschta, Joachim; Schubert, Dirk W. (Polymer Testing, 2018)
Keywords: X-ray diffraction; Isotactic Polypropylene; Processing; Crystallinity; Fourier-transform infrared spectroscopy; Fiber spinning

Development of an embossing process for micro-scale patterns of polypropylene films using statistical design of experiments (DoE) – A strategy to reduce the number of freedom in process settings to find the optimum - Wölfel, Bastian; Schubert, Dirk W.; Lanyi, Franz (Polymer Testing, 2018)
An imprinting process with a brass stamp is used to generate a step on polypropylene plates.Process parameters are systematically varied, temperature, pressing-time, -pressure and the resulting step-heights are determined. Combining the direct correlation of step-height with its variation as a function of process parameters reveals most desirable process parameters. The approach described can be applied to a wide range of processing challenges.
Keywords: Imprinting; Embossing; Polypropylene; Microscale pattern; Optimization strategy

Development of poly(L-lactide) (PLLA) microspheres precipitated from triacetin for application in powder bed fusion of polymers - Dechet, Maximilian; Demina, Anna; Römling, Lea; Gomez Bonilla, Juan Sebastian; Lanyi, Franz; Schubert, Dirk W.; Bück, Andreas; Peukert, Wolfgang; Schmidt, Jochen (Additive Manufacturing, 2020)
In this work, the development and processing behavior of poly(L-lactide) (PLLA) particles for powder bed fusion (PBF) of polymers obtained via a green and sustainable process route are thoroughly studied. Liquid-liquid phase separation and precipitation from triacetin, a non-toxic solvent, are applied for the production of highly spherical PLLA particles of excellent flowability. Starting from the measured cloud-point diagram of the PLLA-triacetin system, appropriate temperature profiles for the precipitation process are derived. The effect of process parameters on the product properties is addressed in detail; the PLLA particles are characterized regarding their size distribution and morphology. Furthermore, material properties including thermal behavior (c.f. processing window for powder bed fusion (PBF)) and powder flowability are assessed. The spherical PLLA particles of narrow size distribution display a wide sintering window of 59 K and an excellent flowability due to the intrinsic surface roughness of the particles. Thus, tensile test bars and complex porous gyroid specimens were successfully manufactured via PBF without the need for any additional surface functionalization of the particles with flow agents. The high potential of the newly developed PLLA powders produced via an environmentally friendly approach omitting the use of halogenated or toxic solvents, as well as flowing aids, is demonstrated by mechanical testing of the printed specimen

Effect of particle rounding on the processability of polypropylene powder and the mechanical properties of selective laser sintering produced parts - Gomez Bonilla, Juan Sebastian; Kletcher, Robin; Lanyi, Franz; Schubert, Dirk W.; Bück, Andreas; Schmidt, Jochen; Peukert, Wolfgang (30th Annual International Solid Freeform Fabrication Symposium - An Additive Manufacturing Conference, SFF 2019, 2019)
Common techniques for the production of polymer powders for selective laser sintering (SLS) involve the comminution of polymers. Comminution of polymers often results in powders made of irregular shaped particles with a low bulk density and a bad flow behavior. With the aim to improve the flowability of grinded powders and, thus, the SLS processability, a thermal process for particle shape modification was developed. This has been applied successfully for a broad variety of thermoplasts. In this contribution, a modified design of a rounding reactor with direct heating and optimized geometry is presented. The performance of the new design is assessed by the rounding of commercially available polypropylene powders. The influence of the rounding process on the packing density, flowability and particle size and shape distributions of the powders is investigated. Test specimens produced by SLS were tested to assess the effect of the rounding process on the mechanical properties of the produced parts. © Solid Freeform Fabrication 2019: Proceedings of the 30th Annual International Solid Freeform Fabrication Symposium - An Additive Manufacturing Conference, SFF 2019. All rights reserve
Keywords: Additives; Comminution; Compressive strength; Laser heating; Particle size; Polypropylenes; Powders; Sintering; Modified designs; Optimized geometries; Packing density; Particle size and shape; Polymer powders; Selective laser sintering (SLS); Shaped particles; Thermal process

Fibre spinning and non-woven evaluation - Voigt, Monika; Lanyi, Franz; Leucker, Karsten; Schubert, Dirk W. (Book of Abstracts, 2016)
Fibre spinning is a very effective technique that allows the continuous manufacturing of fibers. This technique can be applied for synthetic fibers, biopolymers, polymers with additives etc. Furthermore fibers can be structured during the manufacturing process, single fibers as well as bundles. Here we want to give an overview on the basic principles in a pilot spinning machine. Main parameters are the polymer parameters as viscosity, molecular mass, etc. Secondly, process parameters as the through-put, take-up speed, process temperatures (melt/ quenching) and others needs to be controlled. Finally, ambient conditions (temperature/ humidity) play an important role. For the evaluation of the fibre composition and the degradation, there are thermogravimetric analysis (TGA), gel permeation chromatography (GPC), differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy (FTIR) the methods of choice. Mechanical properties determined in single fibre tensile tests need to be investigated as well. The investigation on the linting and pilling behaviour of fibres and textiles are necessary, too. Last but not least, surface energy investigations regarding the wetting of the material and optical characterization to investigate the morphology and related fluid structure interaction are highly relevant for application.

Improvement of polymer properties for powder bed fusion by combining in situ PECVD nanoparticle synthesis and dry coating - Gomez Bonilla, Juan Sebastian; Düsenberg, Björn; Lanyi, Franz; Schmuki, Patrik; Schubert, Dirk W.; Schmidt, Jochen; Peukert, Wolfgang; Bück, Andreas (Plasma Processes and Polymers, 2021)
Polypropylene (PP) powders are coated with silica nanoparticles in a fluidized bed to improve the flow behavior of the powders and the processability in powder bed fusion. The nanoparticles are produced in situ via dusty plasma‐enhanced chemical vapor deposition (PECVD) in an atmospheric‐pressure Ar/O2 plasma jet fixed at the distributor plate of the fluidized bed. Hexamethyldisiloxane is used as a precursor of the nanoparticles. The influence of the oxygen concentration in the plasma gas and the number of treatment cycles on the chemical composition of the nanoparticles, the amount of nanoparticles deposited, and the flow properties of the coated PP powders is investigated. The chemical composition of the formed silica particles is determined by X‐ray photon spectroscopy and infrared spectroscopy. The results reveal that the composition of the nanoparticles is SiOxCy, that is, the portion of organic residues introduced by the precursor can be controlled by changing the oxygen concentration in the plasma gas. The mass of nanoparticles deposited on the polymer powder's surface, as determined by inductively coupled optical emission spectroscopy, shows a linear dependence of the number of cycles and the oxygen concentration in the plasma gas. A considerable improvement of the flow behavior of the PP powders is observed after PECVD treatment.<br
Keywords: nanocomposites; particle coating; plasma‐enhanced chemical vapor deposition; powder bed fusion; powder flowability

Influence of Residence Time and Moisture Content on Molar Mass Dispersity of Polyethylene Terepthalate - Härth, Michael; Lanyi, Franz; Schubert, Dirk W. (Abstracts, 2012)

Mapping, modelling and characterizing multifilament melt-spinning processes in dependence of variable process parameters and the number of dies - Lanyi, Franz; Schrüfer, Stefan; Schubert, Dirk W. (14th Bayreuth Polymer Symposium, 2015)

Novel Chart for Representation of Material Performance and Reliability - Lanyi, Franz; Kunzelmann, Peter; Schubert, Dirk W. (14th Bayreuth Polymer Symposium, 2015)

Novel Chart for Representation of Material Performance and Reliability - Lanyi, Franz; Kunzelmann, Peter; Schubert, Dirk W. (Macromolecular Symposia, 2016)
In modern industrial production lines various process and materialparameters determine the properties of the final product. Thus, a process optimizationprocedure has to take into account a large design space containing several parameters. Asa consequence, the evaluation of the influenceofsingleprocessparametersonthefinalproduct properties can be quite complicated.Usually a certain property of a product, forexample the mechanical strength, has to satisfy a defined specification. In terms ofquality control not only the performance of the material but also the reliability of thespecified values has to be considered. The Weibull statistic gives an interesting approachto evaluate both, material’s performance and reliability. Regarding the mechanicalproperties e.g. in terms of the stress at breaksbthe Weibull analysis leads to acharacteristic failure constantsb,0at which 63.2 % of the samples will break. Additionally,the Weibull modulus m can be regarded as a measure for the width of the distribution ofthe measuring results. High values of m represent a narrow distribution and thus a betterreliability. Moreover, the Weibull modulus m is independent of the absolute value of themeasuring data. Therefore, it is possible to compare samples produced under differentconditions. The standard deviation and the interquartile range are often used to quantifythe scatter of empirical data. It is shown within this work that the Weibull modulus m canbeamoreprecisediscriminatorfortheevaluation of the reliability because it is ratherstable against outlaying values. As an example this study concentrates on the mechanicalproperties of melt spun fibresconsisting of blends from polypropylenes with differentmolar masses produced under various process conditions. This work presents a novelchart which allows one to compare different samples on the basis of the Weibull statisticswhereat the Weibull modulus m is plotted oversb,0. Defining a reference material, them-sb,0-map can be split into quadrants, whereat each quadrant designates animprovement or worsening of material’s performance and reliability with respect to thereference. An evaluation in terms of performance and reliability of great sets of data iseasily applicable. It will be shown that the Weibull statistic can also be applied to Young’sModulus, the elongation at break and the tensile energy absorpti
Keywords: fibers; key performance indicators; mechanical properties; process reliability; Weibull statistics

Novel Chart for Representation of Material Performance and Reliability - Lanyi, Franz; Schubert, Dirk W. (Polychar 23rd, 2015)

Novel method to measure surface crystallinity of fibers and nonwovens - Lanyi, Franz; Schubert, Dirk W. (Europe Africa Conference 2017 of the Polymer Processing Society, 2017)

Novel method to measure surface crystallinity of fibers and nonwovens - Lanyi, Franz; Wenzke, Nicolai; Kaschta, Joachim; Schubert, Dirk W. (54th Nordic Polymer Days, 2017)

On the Determination of the Enthalpy of Fusion of α-Crystalline Isotactic Polypropylene Using Differential Scanning Calorimetry, X-Ray Diffraction, and Fourier-Transform Infrared Spectroscopy: An Old Story Revisited - Lanyi, Franz; Wenzke, Nicolai; Kaschta, Joachim; Schubert, Dirk W. (Advanced Engineering Materials, 2019)
The crystallinity determination of polymers using differential scanning calorimetry (DSC) is a standard procedure in industrial and university research. Its value strongly depends on the enthalpy of fusion, which cannot be determined directly using DSC, but must be calibrated using external methods such as X-ray diffraction (XRD) or density measurements. In addition, the determination of the enthalpy or heat of fusion is not trivial and thus error-prone; hence, values from 60 to 260 J g−1 are quoted for polypropylene in the literature. It is therefore of great relevance to devise a consistent method to determine the heat of fusion. To determine the heat of fusion for polypropylene, a sample set with a broad range of crystallinities is produced using cooling rates between 1 and ≈3500 K min−1. The melting enthalpy of the samples is determined using DSC measurements. The determination of the melting enthalpy based on XRD measurements is discussed in detail, validated using Fourier-transform infrared spectroscopy (FTIR), and compared with values quoted in the open literature. Although two different approaches are used to determine the enthalpy of fusion, a value of 170 ± 3 J g−1 is determined.
CRIS-Team Scopus Importer:2019-11-19
Keywords: differential scanning calorimetry; Fourier-transform infrared spectroscopy; heat of fusion; polypropylenes; X-ray diffraction

Production of polyamide 11 microparticles for Additive Manufacturing by liquid-liquid phase separation and precipitation - Dechet, Maximilian; Goblirsch, Anja; Romeis, Stefan; Zhao, Meng; Lanyi, Franz; Kaschta, Joachim; Schubert, Dirk W.; Drummer, Dietmar; Peukert, Wolfgang; Schmidt, Jochen (Chemical Engineering Science, 2019)
Within this contribution liquid-liquid phase separation (LLPS) and precipitation from ethanol was studied as an approach to produce polyamide 11 (PA11) powders for selective laser sintering (SLS). To this end, the cloud point and solution temperature curve of the PAll-ethanol system was determined experimentally via turbidity measurements. The proper range of system composition and temperature for particle formation was deduced. The dependence of particle characteristics on process parameters (polymer concentration, stirring conditions and temperature regime) during LLPS and precipitation was assessed and the products were characterized with respect to their size and morphology. Furthermore, structural, rheological and thermal characteristics were analyzed and correlated with process parameters. Molecular weight distributions were determined. After removal of fines and dry coating with hydrophobic fumed silica, an optimized PA11 powder with mean particle size of 91 mu m showing good flowability for SLS was obtained. SLS processability of this optimized PA11 powder was demonstrated by building multilayered test specimens in a laser sintering machine. With this contribution, we present a comprehensive workflow for the process development, product characterization and product application of a SLS powder manufactured via precipitation. (C) 2018 Elsevier Ltd. All rights reserved.
CRIS-Team WoS Importer:2019-02-21

Tailored modification of flow behavior and processability of polypropylene powders in SLS by fluidized bed coating with in-situ plasma produced silica nanoparticles - Gomez Bonilla, Juan Sebastian; Trzenschiok, Holger; Lanyi, Franz; Schubert, Dirk W.; Bück, Andreas; Schmidt, Jochen; Peukert, Wolfgang (30th Annual International Solid Freeform Fabrication Symposium - An Additive Manufacturing Conference, SFF 2019, 2019)
The processability of selective laser sintering (SLS) powders and the characteristics of the generated parts depend amongst others on the flowability. To increase the flowability, SLS powders are usually functionalized with flowing agents. Flowing agents are typically applied by dry particle coating. The optimization of the process parameters necessary to achieve a homogenous coating avoiding segregation is still empirical. In this contribution, an alternative process to particle dry coating is presented. This process integrates the synthesis of silica nanoparticles via plasma enhanced chemical vapor deposition (PECVD) and coating of polymer host particles in a fluidized bed in a single process. The influence of the treatment time on the packing density and flow behavior of the powders is investigated. Test specimen are produced to assess the influence of the treatment on the processability of the powders and the mechanical properties of the produced parts. © Solid Freeform Fabrication 2019: Proceedings of the 30th Annual International Solid Freeform Fabrication Symposium - An Additive Manufacturing Conference, SFF 2019. All rights reserve
Keywords: Additives; Coatings; Compressive strength; Fluidized bed process; Laser heating; Nanoparticles; Plasma CVD; Plasma enhanced chemical vapor deposition; Polypropylenes; Powders; Selective laser sintering; Silica; Silica nanoparticles; Sintering; Synthesis (chemical); Alternative process; Dry-particle coating; Fluidized bed coating; Homogenous coatings; Packing density; Process parameters; Selective laser sintering (SLS); Fluidized beds